Study of micro pits on billet experimental surface in extrusion process - Mak, Kam Wong (2015)
Lubrication is very important in cold extrusion of aluminium to reduce the extrusion load and friction. The purpose of this research is to investigate the effects of micro-pits arrays formed on work piece experimental surface and capability of palm oil as a lubricant in cold work extrusion process. Size of pit is 4mm in diameter, 0.4µm in depth and in spherical shape. The pits are separated by 4mm in column and 1mm in row. One palm oil and two additive free mineral oil are used in this experimental work. Two amounts of lubricant are used: 8mg and 15mg.The experimental results are compared to the results obtained from experimental work with work piece without micro-pits. Experimental work with a plain strain extrusion apparatus with a symmetrical work piece is conducted at room temperature. The material of the piece is pure aluminium A1100. The results focused on the extrusion load, surface roughness of work piece experimental surface, flow angle, and flow line. The extrusion load required to extrude work piece with micro-pits lubricated by RBD palm stearin at amount of 8mg was reduced by 11.1 kN compared to work piece without micro-pits. The extrusion load was reduced from 57.7kN to 46.6kN.The results obtained from the experimental work demonstrated that the micro-pits formed on the work piece experimental surface are able to control the friction and palm oil has fulfilled the lubrication performance in paraffin mineral oil. The experimental results also showed that greater amount of lubricant has better performance.